Deformation of large curved shells using double-sided pressure sheet hydroforming process - Wei Liu; Yi-Zhe Chen; Lan Hu; Zhi-Chao Zhang (International Journal of Lightweight Materials and Manufacture, 2022)
Large, thin-walled, and curved surface shells are challenging to deform using traditional forming technologies owing to wrinkling and rupture defects that coexist during the deformation process. In this study, the process of double-sided pressure sheet hydroforming (DSHF) was developed to overcome these issues and fabricate large curved components integrally. A theoretical analysis model was established by considering the stress and strain distributions at varying double-sided pressure ratios during DSHF. Simulations and experiments were conducted using the DSHF process on a hemispherical shell to analyse the effects of the pressure ratio on deformation behaviour, stress and strain, thickness distribution, and deformation defects. Furthermore, a phenomenon called “planar deformation state” was observed, and the stress state was optimised by setting a proper pressure ratio. Under this condition, the thickness distribution was improved and the formed curved shells were free from wrinkling and rupture defects. A CNC sheet hydroforming machine developed by Harbin Institute of Technology was employed to perform a case study of the DSHF process. Lastly, to demonstrate the application of the proposed process, an aluminium-alloy dome with a diameter of 3 m and a uniform thickness distribution was fabricated.